Production of Polyurethane Elastomers from Ximenia americana L (Wild Olive) Seed Oil and Diisocyanates - A. E. Samuel; I. C. Eremosele; S. Y. Kamba; D. S. Samaila (Journal of Applied Sciences and Environmental Management, 2023)
Seed oils readily undergo derivatization by alcoholysis to yield biodegradable polyols and Ximenia americana plant from the family of Olacaeae has oily seeds. Hence, the objective of this paper is to assess the production of polyurethane elastomers from Ximenia americana L (Wild Olive) Seed Oil with diisocyanates, namely, hexamethylene diisocyanate (HDI), toluene diisocyanate (TDI) and 4,4’-methylene diphenyl diisocyanate (MDI) respectively using standard procedure and characterized by Fourier-Transform Infrared Spectroscopy (FTIR), Instron Tensile Testing Machine and Thermogravimetric Analyzer (TGA). The tensile strength and tensile modulus for HDI-based polyurethane elastomers, 5.83±0.15 and 3.95±0.07 MPa respectively are higher than the corresponding ones for TDI- and MDI-based polymers. This is consistent with the highest crosslink density (γ) of 5.05×10-3 for HDI-based polymer with corresponding average molecular weight between crosslinks (Mc) of 197.87 gmol-1  The polyurethane elastomers are stable up to 250-265oC with order of stability: HDPU-1.50>MDPU-1.50>TDPU-1.50. The results showed that diol from Ximenia americana seed oil is effective for production of polyurethane elastomers with properties which are comparable to ones of the non-oil-based polymers.